PENGARUH KESADARAN, PERSEPSI DAN PREFERENSI KONSUMEN TERHADAP PERILAKU KONSUMEN DALAM MENGKONSUMSI BUAH LOKAL STUDI KASUS KAWASAN INDUSTRI DI JAKARTA UTARA - Nira Kurniyanti; Siti Rochaeni; Lilis Imamah Ichdayati (Departement of Agribusiness Faculty of Science and Technology, 2017)
Food is one of should contain nutrient adequacy of the primary needs for human life consisting of healthy and nutritious consumption patterns. The daily food consumption for societies calories, proteins, and vitamins. Consumption is usually gained from staple foods containing much carbohydrates, such as rice and tubers. Meanwhile, proteins are derived from plants and animals while vitamins are obtained from the consumption of fresh fruits. Fruits are source of vitamin that has many benefits for health. Free trade leads to the invasion of imported fruit on the market over time. With the physical qualities, different tastes, and more reasonable prices, some consumers switch to select non-local fruit consumptions. This behavior indicates the person’s perception and the preference shift to consume local fruits. The research was performed in the industrial area in North Jakarta, with the consideration that this place is as the center of industrial activity with the highest productivity value in Jakarta, and the potency as the strategic region bordering with Tanjung Priok port which becomes the center of import-export commodities, especially fruits.